Zdoroven'ki buly! . Zdoroven'ki buly! . Long Live! . Здоровеньки булы! - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. On the Ukrainian diaspora in Russia; The Society of Ukrainian Culture "Slavutych"; the Ukrainian Sunday school in Moscow; problems of national policy in Russia Featured in the program: Kryzhanovskii, Vladimir (Ukrainian Ambassador to Russia); Rudenko-Desniak, Aleksandr (Writer) Contributors: Nazarov, Vladimir (Anchor) Об украинской диаспоре в России; общество украинской культуры "Славутич"; украинская воскресная школа в Москве; проблемы национальной политики в России. В программе участвуют: Крыжановский, Владимир (Посол Украины в России); Руденко-Десняк, Александр (Писатель) Создатели: Назаров, Владимир (Ведущий/Ведущая)